Frequency response of headphones measured in free field and diffuse field by loudness comparison - Hirahara, Tatsuya; Ueda, Kazuo (Journal of the Acoustical Society of Japan (E), 1991)
Loudness comparisons were performed by four subjects, under two experimental conditions: free field (anechoic room) and diffuse field (reverberation room). Each subject adjusted the headphone level of critical band noise bursts until they were equally loud as those from a reference loudspeaker (70dB SPL). Measurement scatter was smaller in the diffuse field than in the free field. To examine the reliability of loudness judg mentsat high frequencies, another method-hearing thresholds by Bekesy tracking-was employed. Each subject's threshold was measured with both loudspeakers and head phones.After compensation was made for the loudspeaker and room transfer functions, headphone frequency response was extrapolated from the results. This method led to high-frequency responses similar to those from loudness comparison. A loudness comparison experiment in which the subjects continuously wore a headphone was performed. However, the method of sound pressure loss measurement should be reconsidered.